System-on-chip sensor fusion front-end self-healing design for network-on-chip digital communications - Seaman, Emmanuel; Du, Jason Yuan (PeerJ Preprints, 2017)
With the ultra-scaling of CMOS technology, high-speed and low-power millimeter-wave communication systems for network-on-chip have been attracting more and more attentions due to the wider bandwidth and higher data rate that can meet the ever-increasing needs for multimedia, massive external data storage, or even biomedical applications. However, from manufacturing’s perspective, the circuits implementations are increasingly susceptible to fabrication process variations with the scaling of CMOS technology, which results in loss of yield rate. To solve this issue, a sensor-fusion solution is proposed in this paper by adding multiple on-chip sensors, including power detectors, temperature sensors, information envelope detectors and related filters, instrumentation amplifiers using a standard CMOS process. These sensors and detectors aim to collect critical system performance and environmental parameters, which will be utilized by a self-healing and optimization algorithm to adjust the state of system components by digitized control knobs.
Keywords: high-speed communication; network-on-chip; system-on-chip; sensor fusion; self-healing; CMOS